Hydraulic modeling concepts and practice - Ettema, R. (Reston, Virginia American Society of Civil Engineers, 2000)
This Manual is intended to serve as a useful reference for people who engage in hydraulic modeling or who directly use the results obtained from hydraulic models. Early chapters provide a brief history of hydraulic modeling, outline strategies for designing models, and explain the underlying concepts of similitude and dimensional analysis. Those concepts are applied subsequently to various situations, beginning with single-phase flow of fluids; water and air are the fluids primarily considered in the Manual. Subsequent chapters address the more complicated situations in which resort must be made to hydraulic models for engineering or technical information. One chapter covers the use of hydraulic models to investigate sediment transport by flow, especially alluvial-sediment transport, and flow in loose-boundary channels. Other chapters cover modeling of gas-liquid flows (notably air in water) and flows involving ice and debris transport. The Manual also addresses hydraulic modeling of situations it terms environmental flows, which essentially encompass buoyancy-modified flows (plumes, stratified flows, mixing) and flow of immiscible fluids (for instance, oil and water). Hydraulic modeling of coastal processes, hydroelastic vibrations, and hydraulic machinery are explained in chapters devoted to those topics. One chapter discusses practical aspects of designing and operating hydraulic models. The Manual's final chapter presents five case study examples.
Includes bibliographical references (p. 361-379) and index.
Keywords: Hydraulic models; Hydraulic models -- Case studies; Electronic books